Development of P5RA Module for Mastering 21st Century Skills of Madrasah Aliyah Students in Medan City - Tadzkia Nasywa Aqmarina; Ummi Nur Afinni Dwi Jayanti (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2025)
Background: The problem in the learning process at Madrasah Aliyah Medan City lies in the use of reference sources, specifically PowerPoint (PPT) modules, that have not been optimally linked to the mastery of 21 St-century skills. This condition has an impact on the learning process, which has not been able to optimally develop students' critical, creative, collaborative, and communicative thinking skills that are very much needed in the current era. This study aims to develop the P5RA module as a learning medium that can improve students' mastery of  21St-century skills. Methodology: The research method used is Research and Development  (R & D) with the 4D model (Define, Design, Develop, Disseminate) to produce a valid and practical module. Validity testing was conducted by involving material experts and media experts, who assessed aspects of the content's feasibility, language, presentation, module size, cover design, and overall module content. Findings: The results of the validity test showed that the percentage of assessment by material experts was 92.91 % and by media experts was  89.92 %. This validity test stage aims to refine the module to meet the criteria for very high validity. The practicality test was conducted through a field trial of the product involving teachers and facilitators as practitioners. The practicality assessment included aspects of the module's attractiveness, usefulness, and relevance to 21 St-century skills. The practicality test results reached a percentage of 91.46 %, categorized as efficient, requiring only minor revisions. Contribution: Based on these results, the developed module has met the feasibility and practicality requirements for use as a learning medium in P5RA activities, supporting students' mastery of 21 St-century skills